Stimulus of socio-cultural factors, internalization, food choice and eating pattern / Mohd Azmin Akbarruddin and Zulhan Othman - Akbarruddin, Mohd Azmin; Othman, Zulhan (2014)
This paper reports the empirical investigation which examines the perception of young women on socio-cultural factors, internalization, and their food choices and eating pattern and comparing the differences of those factors toward body image based on their marital status. Through a descriptive research design using a quantitative method with self-reported and self-administered questionnaires, this study surveyed the young single and married women with an age range from 18 to 35 years old. Results revealed that socio-cultural factors specifically parents, peers and media influence the young women concern of the body image and desire to be having an ideal body figure also influence their food choices and eating patterns. Also, the internalization and perceived pressure to some extent affect the young women body image dissatisfaction and single women exhibit more concern on body figure, social pressure and sources of information on ideal body image and consequently influence their food selection and eating pattern compared the young married women.